Quantifying Energy Level Alignment and Band Gap Movement via Charge Equilibration in Monolayer 2D TMDs/Electrolyte Interface - Almaraz, Rafael; Sambur, Justin (Meeting abstracts (Electrochemical Society), 2025)
2D Transition metal dichalcogenides (TMDs) (MX2; M = Mo, W; X = S, Se) have unique electronic properties that may lead to the next generation of photo-electrocatalysis. The fundamental problem is that the interfacial energetics of TMDs are poorly understood. It is essential that we quantify the behavior of the energy bands in monolayer TMDs to understand the electronic capabilities of this group of semiconductors. In this work, we develop an in-situ absorbance spectroscopy approach to quantify interfacial energetics of 2D semiconductor/electrolyte interfaces using a minimal many-body model to calculate the carrier concentration (n). Our results show that band edge movement in monolayer MoS2 is significant (0.2-0.5 eV) over a narrow range of applied potentials (0.2-0.3 V). Such large band edge shifts could change kET by a factor of 10-100, which has important consequences for practical solar energy conversion applications. In addition, using a combination of in situ spectroelectrochemistry and many-body theory, we quantify the BGR effect magnitude for a ML MoS 2 electrode as a function of solution redox potential. Unlike bulk materials, the E g of a ML MoS 2 electrode changes by over 200 meV upon varying the solution redox potential by 0.8 V. The BGR effect is driven by a charge equilibration process at the semiconductor-redox electrolyte interface that modulates n ; charge equilibration stops when the Fermi level (E F ) of the semiconductor is equal to the redox potential of the solution phase. Our work identifies key fundamental differences between bulk and ML semiconductor|redox electrolyte interfacial energetics and opens new avenues to tune electron transfer kinetics via the BGR effect.